Bioremediation of Artificially Lubricant Contaminated Soil with Manure - Singh, Sandeep (My University, 2014)
Petroleum products are the richest source of energy in the present World. Oil spills during automobile refilling are one of the most common types of soil pollution in the vicinity of oil refilling stations and the main problem is the degradation of such petroleum products. Bioremediation has become an attractive alternative to physicochemical methods of remediation, where feasible. The use of agriculture waste in the form of manure is gaining much importance over microbial isolates in the treatment of oil contaminated sites. The purpose of the use of compost is that it is easy available, containing consortia of microorganisms, increases soil fertility and above all minimization of agriculture residues. In the present study compost was utilized for the treatment of oil contaminated soil. Lubricant oil (5000ppm) was added to sterile soil to form synthetic sample and compost was added in diff. proportions ranging from 0-75%. Early investigation revealed increase in total microbial count and decrease in total petroleum hydrocarbon. Further study will be focused on the physical, chemical and biological parameters of soil containing manure.
M.Tech. (Environmental Science and Technology)
Keywords: Bioremediation; oil; Contaminated Soil; Manure